A comprehensive review: Krill Herd algorithm (KH) and its applications - Bolaji, Asaju La’aro; Al-Betar, Mohammed Azmi; Awadallah, Mohammed A.; Khader, Ahamad Tajudin; Abualigah, Laith Mohammad (Applied soft computing, 2016)
[Display omitted] •The comprehensive review of Krill Herd Algorithm as applied to different domain is presented.•The review covers the applications, modifications and hybridizations of the KH algorithms.•It provides future research directions across different areas. Krill Herd (KH) algorithm is a class of nature-inspired algorithm, which simulates the herding behavior of krill individuals. It has been successfully utilized to tackle many optimization problems in different domains and found to be very efficient. As a result, the studies has expanded significantly in the last 3 years. This paper presents the extensive (not exhaustive) review of KH algorithm in the area of applications, modifications, and hybridizations across these fields. The description of how KH algorithm was used in the approaches for solving these kinds of problems and further research directions are also discussed.